Motivations for Active and Passive Social Media Use and Their Relation to Wellbeing - Gwendolyn Seidman; Lauren M. Hudak; Michael Langlais (Human Behavior and Emerging Technologies)
The present research examined if active and passive social media uses are determined by different motivations and the extent to which these uses and motivations predict wellbeing. Two online surveys (total N=480), one using a sample of adults and the other using an undergraduate sample, showed that active use has two components: self-presentational and other-oriented. In both studies, active self-presentational use was primarily motivated by attention seeking, whereas boredom and fear of missing out (FoMO) were the main motivators for passive use. Both active and passive uses were motivated by a desire for connection. In both studies, connection motives were associated with greater wellbeing, while disconnection motives (assessed in Study 2 only) were associated with poorer wellbeing. FoMO was the most consistent predictor of lower wellbeing, but Study 2 revealed that this association was largely explained by trait loneliness. Attention seeking predicted greater wellbeing and boredom predicted lower wellbeing among the adult but not the college student sample.